Homogeneous dose delivery for very high energy electron beams - Robertson, C (2024)
Very High Energy Electrons (VHEE) are a promising modality for the treatment of deep seated tumours. Advances in accelerator technologies for the Compact Linear Collider have made the production of VHEE beams with a compact machine suitable in a clinical setting feasible. There is interest in using VHEE for dose delivery to deep-seated tumours, as well as inducing the FLASH effect - a phenomenon which selectively spares healthy tissues at ultra-high dose rates. Shaping of the beam to the tumour for conformal treatment is essential. The tumour may be eventually be treated with a single large beam, which would ideally be homogeneous to minimise dose to surrounding healthy tissues. This thesis is concerned with the delivery of such uniform VHEE beams. Magnification of an initially uniform beam to the size of a large tumour using linear optics was demonstrated for e-GaToroid: a novel gantry concept to allow irradiation from multiple angles within a FLASH timescale. This solution required quadrupoles of modest strength and provided high transmission. The TOPAS Monte-Carlo code was used to investigate scattering foils as an alternative method for uniform beam production. Dual-scattering foil design and operation at 200 MeV was studied with a range of setups. Bremsstrahlung emission in the foils required extended beamlines to prevent the loss of uniformity through a water phantom when producing a beam with a homogeneous radius of 75 mm. An automated method for foil design was developed and validated through successive experiments at the CERN Linear Electron Accelerator for Research. This allowed the first measurements of enlarged and flattened VHEE beams to take place. Scattering systems installed in the beamline allowed the evolution of uniform VHEE beams in a phantom to be measured, comparing well with combined RF-Track and TOPAS simulations. The scattering setup is now a permanent upgrade to the user facility.